Nudge or nuzzle? Improving decisions about active citizenship. (3rd March 2016) - Room, Graham
ABSTRACT: In recent years 'nudge' has come into fashion as a form of policy intervention, under the inspiration of behavioural economics. It has encouraged policy analysts to move away from models of the 'rational actor' and instead to start from consumers, clients and citizens as they actually are. Nevertheless, nudge raises larger questions about public policy and the relationship between government and the citizen. This paper takes critical stock of nudge, offers an alternative in terms of 'nuzzle' and lays out the very different standpoint on policy to which this points. In doing so, it also puts in question the disciplinary paradigms which underpin 'nudge' in the scientific literature, and their underplaying of the social and institutional context of individual behaviour. It offers a perspective on public policy as providing security and supporting creativity: with government under critical scrutiny by citizens, rather than vice versa.